Interoperability of Cloud Using Single API (International Journal of Engineering and Computer Science, 2020)
In the cloud computing model, users access services according to their requirements. Most of the people use cloud since it has low cost, high speed computing, backup and restore, mobility and unlimited flexible storage capacity. Cloud resources are hosted in large datacentres operated by companies such as Amazon, Apple, Google and Microsoft. During cloud application deployment, an application is managed over a single service. Such an approach has several short comings. One side-effect of the lack of interoperability among cloud providers is vendor lock in, which means lack of ability to migrate application components from one cloud provider to another cloud provider. If a user finds some required platforms in new service provider but the user cannot leave the current provider as the resources are present with them. This is known as vendor lock in.To solve this issue in achieving interoperability several efforts are underway. Our project is that a user who creates a unique channel that can be used to gain the services provided by different providers. So that the user can use another vendor’s service which is not present in present vendor’s cloud. That is user can use multiple clouds having different resources using a single API without depending on their own APIs.